2014
DOI: 10.1900/rds.2014.11.190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pistachio Nut Supplementation on Blood Glucose in Patients with Type 2 Diabetes: A Randomized Crossover Trial

Abstract: ■ AbstractBACKGROUND: Diabetes is a chronic, potentially debilitating, and often fatal disease. Dietary strategies to reduce postprandial glycemia are important in the prevention and treatment of diabetes. Nuts are rich in mono-and polyunsaturated fatty acids, which may reduce hyperglycemia and improve metabolism. OBJECTIVES: To evaluate the effectiveness of pistachio nut supplementation on glycemic and inflammatory measures in patients with type 2 diabetes. METHODS: In this double-blind, randomized, placeboco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 30 publications
1
99
0
Order By: Relevance
“…However, two studies that examined pistachios reported positive results. Parham et al [18] reported that 12 weeks of pistachio consumption (25g/day) significantly reduced fasting glucose by 0.89 mmol/L and HbA1c by 0.4% compared to a control group in 48 Iranian adults with type 2 diabetes. Hernandez-Alonso et al [27] reported that 4 months of 57g/d of pistachios significantly decreased fasting glucose (−0.29 mmol/l), insulin (−14.2 pmol/L), and HOMA-IR (−0.69) in 54 Spanish adults with pre-diabetes, but did not affect HbA1c.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two studies that examined pistachios reported positive results. Parham et al [18] reported that 12 weeks of pistachio consumption (25g/day) significantly reduced fasting glucose by 0.89 mmol/L and HbA1c by 0.4% compared to a control group in 48 Iranian adults with type 2 diabetes. Hernandez-Alonso et al [27] reported that 4 months of 57g/d of pistachios significantly decreased fasting glucose (−0.29 mmol/l), insulin (−14.2 pmol/L), and HOMA-IR (−0.69) in 54 Spanish adults with pre-diabetes, but did not affect HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to pistachios, a study in young healthy males reported a significant reduction in interleukin-6 and no change in tumor necrosis factor-α or CRP after 4 weeks of treatment [37]. A longer study (12 weeks) in adults with type 2 diabetes reported no effect on CRP [18]. Interestingly, in a sample of adults with pre-diabetes, pistachio consumption for 4 months did not affect circulating measures of inflammation but did reduce lymphocyte gene expression of interleukin-6 [27], suggesting that pistachios may have a nominal effect on inflammation that was not detected in previous work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jenkins and colleagues [156] also found a decrease in insulin secretion in healthy adults and in adults with hyperlipidemia following acute and prolonged almond consumption. Similarly, daily intake of 50.0 g of pistachios for 12 weeks decreased C-reactive protein blood concentrations, systolic blood pressure, and body mass index in adults with T2D [155]. In women with obesity, consumption of peanuts (42.5 g) or peanut butter (42.5 g) as part of a standard breakfast meal increased postprandial insulin blood concentrations and decreased desire to eat following a standard lunch meal [166].…”
Section: Nutritional Modulation Of Glucagon-like Peptide-1 Secretionmentioning
confidence: 99%
“…The pistachio fruit or nut is the edible part of the pistachio plant and is used as flavoring in food and snacks and has been used for therapeutic purposes. Pistachios have a warm and dry nature and contain a large amount of plant protein, starch, unsaturated fats, vitamins, fiber, and minerals such as potassium and magnesium (5)(6)(7)(8). The pistachio is very nutritious and contains vitamins B1, B2, B6, E, and C, calcium, and iron and is effective in boosting physical strength and activity of brain cells (9,10).…”
Section: Introductionmentioning
confidence: 99%